Faktor-Faktor yang Berhubungan dengan Kejadian Diare pada Balita di Kota Tomohon - Hany C Malingkas; Andi Alim; Zamly Zamly; Ekafadly Yusuf (Poltekkes Kemenkes Padang, 2025)
The prevalence of diarrhea remains high in countries with limited access to clean water, sanitation, and personal hygiene. To reduce diarrhea cases, Indonesia has implemented the Community-Based Total Sanitation (STBM) program, with a key indicator being the reduction of open defecation behavior. This study aims to identify the factors associated with the incidence of diarrhea among children under five in Tomohon City. This is an analytical study with a quantitative approach and a cross-sectional design. The population includes 840 children under five in the Lansot Health Center area, with a sample size of 271 children. Data were collected through questionnaires given to the children's parents. Independent variables include the role of sanitation officers, latrine ownership, access to latrine use, and the practice of stopping open defecation (stop BABS). Data were analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses. The results showed significant associations between all independent variables and the incidence of diarrhea. The dominant factors were access to latrines (p = 0.001; OR = 3.838) and stop BABS behavior (p = 0.002; OR = 5.148). It is concluded that improved access and sanitation behaviors significantly reduce diarrhea incidence in children. It is recommended that the community maintain existing sanitation facilities and continue promoting clean and healthy living behaviors to prevent diarrhea in children.